“Regional Environmental Agenda: Port of Baku as a Sustainable Case”- Assessing Port of Baku’s Role in Addressing the Negative Impact of Port Operations and Supporting Sustainable Business Practices - Ahmadova, Iram; Amiraslanova, Sabuha; Mammadov, Ali; Hajiyev, Ibrahim (ADA University, 2024)
Ports are essential entry points for the flow of marine trade and transportation during fast globalization and the unrelenting movement of products across boundaries. Although ports are essential in global trade and transport, the damage they cause to the environment is also inevitable. The "Green Port" project, which aims to reduce the environmental damage caused by ports, has attracted significant interest as a proactive response to increasing environmental concerns and the need for sustainability in port operations. The Port of Baku, which has a crucial position today in global connectivity, is one of the ports with Green Port certification. Considering that the shift to green port projects is not without difficulties, this research aims to analyze the challenges of implementing green port projects in the Port of Baku. The study has revealed that to carry out green port projects and decrease the negative impacts of port operations, there is a lack of technical advancement, investment, skill awareness, or experts in the field. The study proposes policy solutions for each challenge - an attractive investment climate, implementing skills development and technical advancement standards, private sector involvement in port operations, a standardized approach to sustainability reporting, and Port of Baku performance verification. These solutions are evaluated based on five main criteria: effectiveness, efficiency, equity, feasibility/implementability, and flexibility/improvability. The research drew uponsecondary data sources and conducted semi-structured interviews with experts in the field. The analysis and assessment indicate that the Port should implement sustainability reporting frameworks to enhance green port projects. These frameworks are essential for effective sustainability management and for boosting the Port’s appeal to investors.
Keywords: Ports -- Environmental aspects -- Azerbaijan -- Baku.; Green technology -- Ports -- Azerbaijan; Caspian Sea -- Environmental aspects; Climate change mitigation; Public and International Affairs